Association between pathological and MRI findings in multiple sclerosis. Issue 2 (February 2019) - Filippi, Massimo; Brück, Wolfgang; Chard, Declan; Fazekas, Franz; Geurts, Jeroen J G; Enzinger, Christian; Hametner, Simon; Kuhlmann, Tanja; Preziosa, Paolo; Rovira, Àlex; Schmierer, Klaus; Stadelmann, Christine; et al.
Summary: Pathological evaluation is the gold standard for identifying processes related to multiple sclerosis that explain disease manifestations, and for guiding the development of new treatments. However, there are limitations to the techniques used, including the small number of donors available, samples often representing uncommon cases, and impossibility of follow-up. Correlative studies have demonstrated that MRI is sensitive to the different pathological substrates of multiple sclerosis (inflammation, demyelination, and neuro-axonal loss). The role of MRI in evaluating other pathological processes, such as leptomeningeal involvement, central vein and rim of lesions, microstructural abnormalities, iron accumulation, and recovery mechanisms, has been investigated. Although techniques used for quantifying pathological processes in different regions of the CNS have advanced diagnosis and monitoring of disease course and treatment of multiple sclerosis, new perspectives and questions have emerged, including how different pathological processes interact over the disease course and when remyelination might occur. Addressing these questions will require longitudinal studies using MRI in large cohorts of patients with different phenotypes.